The complete mitochondrial genome sequence of Hemibagrus sp. (Siluriformes: Bagridae), molecular data for species identification. (3rd May 2016) - Zhou, Can-Lin; Tian, Juan; Yang, Chang-Geng
Abstract: In this study, we determined and described the complete mitogenome sequence of Hemibagrus sp. for the first time, which is 16, 513 bp in length, and contains 37 genes, including 13 protein-coding genes, 2 rRNAs, 22 tRNAs, 1 origin of replication on the light-strand (OL ) and a putative control region. The overall base composition was 31.1% A, 26.9% T, 26.9% C, 15.1% G, with a slight AT bias (58.0%). All protein-coding genes shared the start codon ATG, except for COI, which began with GTG. The tRNA-Ser UGC couldn't be folded into the typical cloverleaf secondary structure because its dihydrouridine arm is replaced by a simple loop. These results are expected to provide useful molecular data for species identification and further phylogenetic studies of Bagridae and Siluriformes.